The Effects of Privatization and Ownership in Transition Economies - Estrin, Saul; Hanousek, Jan; Kočenda, Evžen; Svejnar, Jan (Journal of Economic Literature, 2009)
In this paper, we evaluate what we have learned to date about the effects of privatization from the experiences during the last fifteen to twenty years in the postcommunist (transition) economies and, where relevant, China. We distinguish separately the impact of privatization on efficiency, profitability, revenues, and other indicators and distinguish between studies on the basis of their econometric methodology in order to focus attention on more credible results. The effect of privatization is mostly positive in Central Europe, but quantitatively smaller than that to foreign owners and greater in the later than earlier transition period. In the Commonwealth of Independent States, privatization to foreign owners yields a positive or insignificant effect while privatization to domestic owners generates a negative or insignificant effect. The available papers on China find diverse results, with the effect of nonstate ownership on total factor productivity being mostly positive but sometimes insignificant or negative.